Perlindungan Hukum terhadap Anak yang Belum Dewasa Akibat Kehilangan Orang Tua - Ilyas Ilyas (Universitas Syiah Kuala, 2011)
ABSTRACT: Based on Indonesian law, a guardian is responsible for the walfare and property of the children under his guardianship including the heritage. In Aceh, usually a guardian is a man in the child’s father family and generally he is only responsible to manage the property of the child under his guardianship but the walfare and day care s still the responsibility of the mother. However, if the mother also die the guardianship is given to the family of the mother. This research aims to explain what the authority of the guardian towards the child means to represent the child is and the constraints of the guardian in conducting the guardian for children in terms of providing the protecting for the child. The research shows that the authority of the guardian towards the child means to represent the child in acting in relation to the property of the parent and benefit the child, the guardian has an obligation to manage the property. The constraint factors to be a guardian for the child are of the understanding of the guardian obligation. Law Protection on Orphans Losing Their Parents